2017
DOI: 10.1177/1367493517715147
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of collecting psychosocial data from fathers of very low birth weight infants

Abstract: The aim of this study was to determine the feasibility and acceptability of collecting outcome data from parents of very low birth weight (VLBW) infants and to explore the psychological and social adaptation of fathers. Questionnaires were distributed to 38 parents of VLBW infants and 36 parents of term infants within a hospital Neonatal Intensive Care Unit. Field notes were also taken. Parents indicated collecting outcome data in this population was feasible and acceptable, but barriers and difficulties in da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Parent perspectives were reported in eight studies (34,49,(78)(79)(80)(81)(82)(83); nine reported health professional perspectives (84)(85)(86)(87)(88)(89)(90)(91)(92); none included both. A further three feasibility and implementation studies reported behavioral indicators (e.g., completion rates) without collecting participants' perspectives (93)(94)(95).…”
Section: Overview Of Included Acceptability Studiesmentioning
confidence: 99%
“…Parent perspectives were reported in eight studies (34,49,(78)(79)(80)(81)(82)(83); nine reported health professional perspectives (84)(85)(86)(87)(88)(89)(90)(91)(92); none included both. A further three feasibility and implementation studies reported behavioral indicators (e.g., completion rates) without collecting participants' perspectives (93)(94)(95).…”
Section: Overview Of Included Acceptability Studiesmentioning
confidence: 99%
“…Being able to express experience using metaphors can help both parents and those who care for them to make sense of this experience, enabling a poignant and evocative way to communicate. This is vital, given the evidence on the emotional turmoil experienced by parents and the challenges in relation coping with the stress and uncertainty of having a sick, premature baby (Spinelli et al, 2016; Turner et al, 2014) when emotional support can sometimes be perceived to be lacking (Bagge et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study of fathers who experienced a traumatic birth and met some PTSD criteria suggested that the subjective nature of the perception of the birth was crucial and this may have implications for the development of PTSD symptomology (Etheridge & Slade, 2017). Recent work has shown that it is feasible and acceptable to fathers to administer multiple research questionnaires when investigating this area (Bagge, Westgate, Few, Clarke, & Adlam, 2017). The use of mixed methods designs could help to unravel the highlighted complexities with regards to the degree to which PTSS is related to the Page 17 of 28 experience of the preterm birth relative to the protracted NICU hospitalisation.…”
Section: Future Researchmentioning
confidence: 99%